The Effects of Individual Psychotherapy in BDNF Levels of Patients With Mental Disorders: A Systematic Review - Claudino, Felipe Cesar de Almeida; Gonçalves, Leonardo; Schuch, Felipe Barreto; Martins, Hugo Roberto Sampaio; Rocha, Neusa Sica da (Frontiers in Psychiatry, 2020)
Background: Brain-derived Neurotrophic Factor (BDNF) is considered the main cerebral neurotrophin and is produced in the central neural system and peripherals. Its levels are reduced in patients with several psychiatric disorders, but it is unclear if the response to psychotherapy can alter its concentration. Objective: To carry out a systematic review evaluating the effects of individual psychotherapy in BDNF levels in patients with mental disorders. Methods: The databases PubMed, EMBASE, PsycArticles, SciELO, Web of Science, and CENTRAL; the last search was performed on October, 2019 for trials evaluating the effects of individual psychotherapy in BDNF levels in adults with mental disorders. PROSPERO registration: CRD42018108144. Results: Eight of 293 studies were included. A rise in BDNF levels was observed in depressive patients when psychotherapy was combined with medication. Patients with PTSD who responded to therapy presented a raise in BDNF levels mostly when combined with physical activity. There was a rise in BDNF levels in those who responded to psychotherapy in patients with bulimia, in borderline patients, and in insomniacs. Conclusions: The BDNF seems to present variations after psychotherapy especially in patients with bulimia, PTSD, insomnia, and borderline. These subjects also have symptom reduction. Thereby, BDNF could be a supplemental tool to analyze the success to psychotherapy. BDNF levels in patients with major depression after therapy are still controversial and the short follow-up of most studies is a limiting factor.